ANALISIS RESPON SISWA MTs. ASSA'ADAH II BUNGAH GRESIK TERHADAP PEMBELAJARAN TATAP MUKA TERBATAS SELAMA PANDEMI - Olivia Nathania Delviana; Vela Ayu Wulandari; Alfiatur Rohmah; Nurul Waqidah; Ita Ainun Jariyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The Covid-19 pandemic, which is now starting to subside, has caused the government to allow several regions to reopen face-to-face activities, although on a limited basis, one of which is MTs. Assa'adah II Bungah Gresik. The policy will certainly get a response from students in the face of new learning activities. This study aims to determine the responses of MTs students. Assa'adah II Bungah Gresik regarding limited face-to-face learning during the pandemic. The subjects of this study were MTs students. Assa'adah II Bungah Gresik as many as 127 students. The data collection technique used is in the form of a questionnaire (questionnaire) in the form of a google form which is distributed online. The results showed that during limited face-to-face learning, learning was more fun, the face was more enthusiastic in learning, comfort was more secure, the material was easier to understand, the quality of learning was better, facilitated interaction between teachers and friends, and the minimum difficulties experienced by students. Students also agree to the face-to-face policy made by the government while still paying attention to health protocols during the learning process. Compared to bold learning, students feel bored and less enthusiastic in learning activities. Students often feel bored because of limited interaction with friends. The explanation of the material is not optimal due to the limited interaction between teachers and students. Inadequate facilities also affect learning activities.